Gender Disparities in Technological Proficiency Among Women Online Workers in the Digital Economy Era - Deselia, Sanita; Hariati Sinaga (HUMANISMA : Journal of Gender Studies, 2024)
This research examines the themes of women's digital literacy within the evolving digital economy. Digital literacy includes the ability to operate technological devices, critical understanding on information, and the use digital media safely and effectively. The literacy is one of the crucial keys to succeed in the competitive market, particularly for online women workers. This literature study employs descriptive analysis from a feminist political economy perspective that analyzes how power relations, social structures, and the economy shape gender inequality in the context of work and technology. This analysis explores the technology gap among women online workers, focusing on challenges, opportunities, and skills gaps. The findings indicate that in the era of the digital economy, technological proficiency is one of the keys to enhance women's livelihood. Nevertheless, women tend to possess lower technological skills than men. Several factors contribute to this gap, including socio-cultural structures, gender-biased technology, and limited access to education. It is essential to implement appropriate policies and initiatives to improve women's digital literacy, so, we can empower women to compete in the digital economy.